(untitled) (Docentes 2.0 Journal, 2021)
In the last 20 years, little has fueled the growth of musical, artistic research. To develop this type of research, the teacher needed to adapt the curricular programming and the curricular plans that have not been contextualized for various academic reasons at the National University of Frontera. This research aimed to propose a contextualized curricular program that develops musical, artistic research in administration, hotel, and tourism students. In this study, four research questions arose: how to identify the development of artistic research? What theoretical foundations should be considered to characterize the program? How to validate it? And what aspects to consider? which gave rise to a proposed non-experimental, propositional quantitative methodology. Three questionnaires were developed; these were applied to 27 students, six hierarchical, two teachers. In this research, three questionnaires of 9 questions were used: the students, hierarchies, and teachers who taught the art course this semester. It concluded that musical, artistic research is not promoted because of the teachers assigned to teach the art course; only 50% are from the specialty. The curricular programs and syllables are not contextualized for the development of musical, artistic research. They have not promoted training projects in the area in question.